TECHNIQUES FOR DETERMINING BREAKS IN A MAGMA CONDUIT - Ivanov A.I. (My University, 1997)
Techniques are proposed for determining stresses that are produced in a volcanic edifice by pressure in the central conduit and its own weight and locating a region in the edifice where a break is likely to occur. The location and direction of a fissure in the wall of the central conduit is found using an improved formulation of the Coulomb-Mohr criterion that the author put forward earlier.